Selenoprotein W1 (SEPW1) Gene Polymorphism and Association with Mineral Content in Sheep - Astira, Adinda Wanda; Harahap, Ratna Sholatia; Sumantri, Cece; Gunawan, Asep (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2023)
Selenoprotein W1 (SEPW1) is a protein containing selenium that has an important role in muscle growth and development by protecting myoblasts from oxidative stress. This study was aim to identify the diversity of the SEPW1 gene and its association with mineral content in sheep. The samples used were 100 sheep consisting of 10 samples of compass agrinak sheep (CAS), 15 samples of Javanese fat-tailed sheep (JFT), 30 samples of Javanese thin-tailed sheep (JTT), 25 samples of garut composite sheep (GCS), and 20 samples of jonggol sheep (JS). Selected mineral contents were determined using the IK method LP-04.10-LT-1.0. Identification of SEPW1 gene polymorphism will be conducted using Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP). The size of the amplification product was 455 bp. Chi-square analysis showed that the population was in Hardy-Weinberg equilibrium. Polymorphism of the SEPW1 gene was found in each breed of sheep. The SEPW1 gene’s SNP g.53617063 A>G was significantly (p